Enhancing Spatial Intelligence through Map Media in Elementary Social Studies - Adelia Mohamad (PT MEDIA JURNAL DAN PENDIDIKAN, 2025)
Spatial intelligence is a crucial aspect of social studies education that often lacks optimization due to passive learning methods and inadequate media use. This study aims to explain the application of social studies learning in improving students' spatial intelligence through the enhancement of teachers' ability to prepare lessons, specifically utilizing map media in class V at SDN 07 Marisa. The research employed a qualitative descriptive design, with data collected through direct observation and document study involving the school principal and class teachers. Data were analyzed using interactive models comprising data reduction, data display, and conclusion drawing. The results indicate a significant difference in student spatial comprehension when teachers competently utilize map media compared to conventional teaching. The integration of map media effectively transitions learning from an abstract concept to a concrete experience, thereby avoiding verbalistic knowledge and increasing student engagement in understanding geographical elements. In conclusion, the appropriate use of learning media in social studies significantly enhances students' cognitive, affective, and psychomotor skills regarding spatial intelligence.